Developing a Better Clinical Alert System in EHRs. Issue 1 (June 2015) - Mauney, Jennifer; Furlough, Caleb; Barnes, Janey
Currently, many alert systems designed for EHRs can negatively affect providers' ability to prescribe appropriately and thus, are also affecting patient safety. This is due to the design of the alerts and the overwhelming number of alerts presented. There is a wealth of information in the human factors literature on the design and use of alerts but that information is either not known or has not been implemented in the design of EHRs. This paper will bring that literature to light, and demonstrate how to implement the recommendations to develop not only a better system for handling alerts in EHRs, but better CPOE (Computerized Provider Order Entry) as well. Serious usability issues with medication-based alerts displayed on EHRs were found after reviewing the data from the Meaningful Use 2 (MU2) Usability reports linked to the ONC CHPL website. The types of alert system issues found within the MU2 Usability reports and across various EHR vendors as well as human factors research that specifies how to deal with these issues will be described in this paper. In addition, recommendations for the design of medication-based alerts will be presented.